ANTAGONISM AND SUBJECTIFICATION IN THE POEM OF RESISTANCE. - Casas, Arturo (Cosmos & History, 2010)
This article offers a pragmatic and relational analysis of the controversial heuristic of cultural resistance and presents some of the problems that affect the production and distribution of the poetic discourses of resistance and emancipation. To that end, it focuses on the incorporation of the historicity and the historic contingency of conflict as key elements of the subjectification constituted by the poem of resistance as “poem for the political”. It also explores the applicability of certain notions common to the contemporary critical tradition, as developed by scholars such as Badiou, Mouffe, Rancière, Bal and Žižek